The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0103-50532000000600008
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of flower rewards -- Oncidium (Orchidaceae)

Abstract: A maioria dos estudos sobre polinização focalizam as interações que envolvem recompensas como néctar e pólen. Nosso grupo de pesquisa, entretanto tem se dedicado à química de recompensas florais como resinas e óleos florais. Neste trabalho, estamos relatando a composição química dos óleos florais de Oncidium pubes que contêm di e triacilglicerois nos quais o glicerol está esterificado com um ou dois resíduos de ácido acético e um ácido graxo. O padrão de substituição dos dracilgliceróis foi sugerido com base n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…They were detected in amounts lower than 1% ( Table 2). Some of these compounds were also reported from Oncidium oil (Reis et al, 2000). EI mass spectra of 1-acyl-2,3-diacetyl-glycerols were also previously described (Reis et al, 2003).…”
Section: Ei-ms Analysis Of the Acylglycerols Of Diascia Oilsmentioning
confidence: 97%
See 1 more Smart Citation
“…They were detected in amounts lower than 1% ( Table 2). Some of these compounds were also reported from Oncidium oil (Reis et al, 2000). EI mass spectra of 1-acyl-2,3-diacetyl-glycerols were also previously described (Reis et al, 2003).…”
Section: Ei-ms Analysis Of the Acylglycerols Of Diascia Oilsmentioning
confidence: 97%
“…doi:10.1016/j.phytochem.2007.12.012 b-acetoxy fatty acids were found as main lipid components (Vogel, 1969(Vogel, , 1974(Vogel, , 1986(Vogel, , 1990Simpson et al, 1977Simpson et al, , 1979Seigler et al, 1978;Cane et al, 1983;Simpson and Neff, 1983;Buchmann, 1987;Vinson et al, 1997). The structure of a novel diacylglycerol of Ornithophora radicans was elucidated from spectroscopic data (Reis et al, 2000(Reis et al, , 2003. Our group was first to report partially acetylated 3,7-dihydroxy fatty acids as a new type of constituent in Malpighia coccigera (Malpighiaceae) oil; and to discuss a possible relationship between floral oil and plant epicuticular wax biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Flower pollination occurs during floral oil collection 2 and we were thus motivated to study the chemical composition of floral oils belonging to 30 different species of the subtribe Oncidiinae. We have found that the major components of the floral oils of Oncidium pubes Lindl., 3 4 Asymmetrically substituted diacylglycerols are known to activate the protein kinase C (PKC), responsible for the cellular signal transductions that promote lipid hydrolysis and phosphorylation of a variety of target proteins which control growth and cellular differentiation. 5 Therefore the role of these floral oils in the bees% lives may be more important than just nest material.…”
mentioning
confidence: 99%
“…The oils of certain other members of the 'Gomesa clade' such as Oncidium enderianum auct. and related taxa also contain diacylglycerol derivatives but here, the compounds are not exuded (Reis et al, 2000).…”
Section: Trichomal Elaiophoresmentioning
confidence: 87%
“…and Zygostates lunata Lindl. (Reis et al, 2000(Reis et al, , 2003 although, remarkably, that of P. delicatulum is composed largely of linear hydrocarbons . The major component of the floral oil of Ornithophora radicans is (2S, 3'R, 7'R)-1-acetyl-2-(3', 7'-diacetoxy-eicosanoyl)-glycerol (Reis et al, 2003) and acylglycerols are thought also to occur in the floral oils of Oncidium loefgrenii Cogn.…”
Section: Trichomal Elaiophoresmentioning
confidence: 98%